Graphene-like carbon nanosheets grown over alkali-earth metal oxides : effects of chemical composition and physico-chemical properties - Chen, Wen Qian (2021)
Catalytic effects of alkali-earth metal oxides (MgO, CaO, SrO and BaO) on the growth of graphene-like carbon nanosheets via catalytic chemical vapor deposition of ethanol at 950 °C under atmospheric pressure were investigated. Both commercially available alkali-earth metal oxides as well as three synthetic MgO catalysts were used in this study. Chemical composition and physico-chemical properties, such as morphology, crystal surface geometry and porosity of catalysts were demonstrated to influence the yield and quality of graphene-like carbon nanosheets. Among investigated oxides, the MgO, CaO and SrO displayed different catalytic ability towards the growth of graphene-like carbon nanosheets determined by chemical compositions. The effect of physico-chemical properties was suggested by different properties of carbon products over synthetic MgO. MgO catalysts synthesized with ammonia produced the lowest defect level (ID/IG = 0.26) while MgO synthesized with urea and ethylene glycol produced the highest yield (12.1% per catalyst mass) of graphene-like carbon nanosheets compared to the other catalysts. The lower defect level and higher graphitization degree were attributed to well-defined morphology with uniform oxide crystal particle size and improvement of crystal orientation along (200) lattice plane in the catalyst. The higher yield was related to the higher porosity of catalysts.